Irreducibility Endogenised - Delorme, Robert (Journal of Public Governance, 2011)
The author of the present work, which constitutes an excerpt from his book Deep Complexity and the Social Sciences. Experience, Modelling and Operationality, offers a detailed analysis of an intrinsic irreducibility of risk of accidents in complex systems. Drawing on the works of authors such as Charles Perrow, he argues that the fundamental reason behind such events is the unpredictability of interactions between individual components of these systems. He goes on to outline the concept of defences-in-depth and criticises it on the grounds of the ever-growing distance between operators and the systems that they are supposed to supervise, and the occurrence of the so-called latent problems. The selected fragment of the book concludes with a presentation of different points of view on the subject of defining socially acceptable levels of risk and its optimisation with reference to the theoretical model of compromise between risk and performance proposed by James Reason, along with a discussion of the practical application of the precautionary principle.